High-titanium blast furnace slag glass ceramic and preparation method thereof
By preparing high-titanium blast furnace slag microcrystalline glass, utilizing the heat recovery of the rolling roll and using TiO2 and ZrO2 as nucleating agents, the problems of low titanium element utilization and heat energy waste in high-titanium blast furnace slag are solved, realizing efficient resource utilization and heat energy recovery, and producing high-performance microcrystalline glass.
Patent Information
- Application Number
- CN202511474001.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2025-11-28
AI Technical Summary
Existing technologies show that the utilization rate of titanium resources in high-titanium blast furnace slag is low and thermal energy is wasted seriously. Traditional treatment methods pose environmental pollution risks and high energy consumption problems.
Microcrystalline glass is prepared by using high-titanium blast furnace slag and external raw materials with similar composition. The heat energy of the high-temperature molten liquid is recovered by utilizing the heat exchange function of the rolling roll, and crystallization is promoted by using TiO2 and ZrO2 as composite nucleating agents to prepare high-performance microcrystalline glass.
This method enables the resource utilization of high-titanium blast furnace slag, improves the recovery rate of titanium resources, reduces the risk of environmental pollution, and effectively recovers thermal energy to produce microcrystalline glass with high flexural strength.
Smart Images

Figure CN121020993A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of comprehensive utilization of solid waste, and particularly relates to a high-titanium blast furnace slag glass-ceramic and a preparation method thereof. BACKGROUND
[0002] The resource utilization of high-titanium blast furnace slag is a key challenge in the field of mineral smelting slag treatment. Panxi region in China is the main production area of vanadium-titanium magnetite, and the high-titanium blast furnace slag (TiO2 content of 18%-25%) generated in the smelting process has important recycling value. The current treatment method widely used in industry is to quench the high-temperature molten slag at 1350-1500℃ by water or air cooling, and then use it as an admixture for cement or concrete. However, this traditional treatment method has two outstanding problems: on the one hand, a large amount of heat energy contained in the high-temperature molten slag cannot be effectively recovered and utilized; on the other hand, the titanium element in the blast furnace slag exists in the form of stable compounds, resulting in low resource utilization rate. In order to improve the recovery rate of titanium resources, researchers have developed acid leaching of titanium and high-temperature carbonization-low-temperature chlorination to prepare TiCl4, etc. However, these methods have many limitations in practical application: acid leaching process produces a large amount of acid-containing wastewater, which poses an environmental pollution risk; and the chlorination process is difficult to realize industrialization due to its complex process and high energy consumption. In view of these defects in the existing technology, it is of great significance to carry out research on the efficient treatment and resource utilization of molten high-titanium blast furnace slag.
[0003] Glass-ceramic is a kind of polycrystalline solid material prepared by precisely controlling the crystallization process of base glass, and its microstructure is composed of uniformly distributed microcrystalline phase and glass phase. This kind of material is widely used in many fields such as building decoration, household goods, electronics, chemical industry and automobile manufacturing due to its excellent chemical stability, outstanding mechanical properties and good wear resistance. From the chemical composition, the main components of traditional glass-ceramic are CaO-SiO2-Al2O3 system, which has a high similarity with the chemical composition of high-titanium blast furnace slag. It is worth noting that TiO2 contained in high-titanium blast furnace slag is not only an efficient fluxing agent, but also an excellent nucleating agent, which provides technical advantages and development potential for the preparation of high-performance glass-ceramic using high-titanium blast furnace slag.
[0004] In order to solve the problems of low resource utilization rate of titanium element in high-titanium blast furnace slag and waste of a large amount of heat from molten blast furnace slag in the existing technology, an effective resource utilization method of high-titanium blast furnace slag is urgently needed. SUMMARY
[0005] An object of the present application is to at least solve the above problems or deficiencies and provide technical solutions which will be described later.
[0006] To achieve the objects and other advantages and in view of its purposes, the application provides a high-titanium blast furnace slag glass-ceramics, including 60.0-90.0wt% high-titanium blast furnace slag, 10.0-40.0wt% additional raw materials, the final chemical composition of the high-titanium blast furnace slag glass-ceramics including 15-25wt% CaO, 30-45wt% SiO2, 10-20wt% TiO2, 10-20wt% Al2O3, 1-7wt% MgO, 1-4wt% Fe2O3, 1-10wt% ZrO2, and the sum of each component being 100wt%.
[0007] Preferably, the phase composition of the high-titanium blast furnace slag includes 10wt%-30wt% CaO, 10wt%-30wt% SiO2, 10wt%-25wt% TiO2, 10wt%-20wt% Al2O3, 0-15wt% MgO, 0-5wt% Fe2O3, and the additional raw materials include 1-8wt% CaO, 8-18wt% SiO2, 0-3.7wt% Al2O3, 0-2.3wt% MgO, 1-8wt% ZrO.
[0008] Preferably, the TiO2 and ZrO2 can be used as a nucleating agent alone, and the TiO2 and ZrO2 form a composite nucleating agent, which has a strong influence on the phase transition dynamics of the glass, exceeding the effect when used alone; the SiO2 can construct a stable silicon-oxygen tetrahedral network and is a basic framework material of the glass-ceramics.
[0009] The application also provides a preparation method of the high-titanium blast furnace slag glass-ceramics, including the following steps: Step one, the additional raw materials are weighed according to the proportion, mixed and then added into the high-titanium blast furnace slag high-temperature molten liquid to obtain a high-temperature glass liquid; Step two, the high-temperature glass liquid is calendered by a calendering roller with heat exchange function to obtain a base glass; Step three, the formed base glass sample is directly subjected to nucleation and crystallization heat treatment by using the heat energy obtained by the calendering roller with heat exchange function to obtain a glass-ceramics sample.
[0010] Preferably, in the step one, the temperature of the high-titanium blast furnace slag high-temperature molten liquid is 1350-1500℃, and no external heating is needed after the additional raw materials are added.
[0011] Preferably, in the step two, the high-temperature glass liquid is directly formed by the calendering roller with heat exchange function without pouring into an external mold, the calendering roller contains heat exchange medium in the roller body, the heat exchange medium absorbs and transports the heat energy to the furnace for collecting heat after the high-temperature glass liquid passes through the calendering roller, and finally, the formed base glass can be directly subjected to nucleation and crystallization treatment by using the heat energy obtained by exchange.
[0012] Preferably, in the step two, the calendering roller with heat exchange function contains heat exchange medium in the roller body, and the heat exchange medium is one of water, oil and gallium.
[0013] Preferably, in the step one, before the additional raw material is added into the high-temperature molten liquid of high-titanium blast furnace slag, the zirconia in the additional raw material is modified by the following method: S11, the zirconia, yttrium oxide and beryllium hydroxide are mixed and then high-energy ball-milled, and then filtered to obtain a mixture; S12, the mixture, polyacrylamide and sodium bicarbonate are added into water, heated and stirred, and then filtered and washed after cooling to obtain a zirconia-yttrium oxide nucleating agent.
[0014] Preferably, in the S11, the mass ratio of the zirconia, yttrium oxide and beryllium hydroxide is 1:0.05-0.10:0.01-0.02, the high-energy ball-milling parameters are as follows: yttrium-stabilized zirconia balls are used, the ball-to-material ratio is 8-10:1, the ball-milling medium is liquid nitrogen, and the ball-milling is performed at a speed of 600-800 rpm for 2-4 h.
[0015] Preferably, in the S12, the mass ratio of the mixture, polyacrylamide, sodium bicarbonate and water is 1:0.1-0.2:0.05-0.10:10-20, and the heating is performed as follows: first heated and reacted at 50-80 DEG C for 1-2 h, and then reacted at 130-135 DEG C for 0.5-1 h.
[0016] The present application has the following beneficial effects: the present application uses high-titanium blast furnace slag as raw material, adds additional raw material highly similar to the composition of the high-titanium blast furnace slag to prepare the glass-ceramics, fully utilizes the heat energy generated by the high-titanium blast furnace slag, reduces the cost of preparing the glass-ceramics by melting method, and realizes heat recycling; the TiO2 and ZrO2 are combined to form a composite nucleating agent which has a strong influence on the phase transition dynamics of the glass, can convert the titanium resource in the high-titanium blast furnace slag into glass-ceramics with high bending strength, realizes the resource utilization of solid waste, and reduces environmental pollution; can provide a new way and idea for the utilization of high-titanium blast furnace slag; the raw material is easy to obtain, the operation is simple, and the present application can be industrialized, mass-produced, has high application value and application prospect. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 It is the technical roadmap of the present application. Figure 2 This is a schematic diagram of the internal heat exchange of the calendering roll of the present invention. Detailed Implementation
[0018] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments, so that those skilled in the art can implement it based on the description.
[0019] Example 1 A method for preparing high-titanium blast furnace slag microcrystalline glass, the technical roadmap of which is as follows: Figure 1 As shown, it includes the following steps: Step 1: Weigh out 1 wt% CaO, 8 wt% SiO2 and 1 wt% ZrO2 as external raw materials. Mix the external raw materials and add them directly to 90 wt% high-titanium blast furnace slag high-temperature molten liquid (1450℃) to obtain high-temperature glass liquid with a viscosity of 0.386 PaS. Step 2: Pass the high-temperature molten glass through a rolling mill roll with heat exchange function (such as...) Figure 2 (As shown), it is rolled into shape to obtain the base glass; Step 3: The formed base glass sample is directly subjected to nucleation and crystallization heat treatment using the heat energy exchanged by the calendering roller with heat exchange function to obtain a microcrystalline glass sample. The average flexural strength of the six groups of microcrystalline glass samples is 145.62 MPa, and the main crystalline phase precipitated is monoclinic pyroxene (Esseneite).
[0020] Example 2 The difference between this embodiment and Embodiment 1 is that the raw material ratio in this embodiment is: 80wt% high-titanium blast furnace slag high-temperature molten liquid; 3wt% CaO, 10wt% SiO2, 2wt% Al2O3, 2wt% MgO, and 3wt% ZrO2 as added raw materials. The viscosity of the high-temperature glass melt in this embodiment is 0.421 PaS, the average flexural strength of the six groups of microcrystalline glass samples is 126.62 MPa, and the precipitated main crystalline phase is monoclinic pyroxene (Esseneite).
[0021] Example 3 The difference between this embodiment and Embodiment 1 is that the raw material ratio in this embodiment is: 70wt% high-titanium blast furnace slag high-temperature molten liquid; 7wt% CaO, 13wt% SiO2, 3wt% Al2O3, 2wt% MgO, and 5wt% ZrO2 as added raw materials. The viscosity of the high-temperature glass melt in this embodiment is 0.480 PaS, the average flexural strength of the six groups of microcrystalline glass samples is 94.09 MPa, and the precipitated main crystalline phase is fassaite-like mineral.
[0022] Example 4 The difference between this embodiment and Embodiment 1 is that the raw material ratio in this embodiment is: 60wt% high-titanium blast furnace slag high-temperature molten liquid; 8wt% CaO, 18wt% SiO2, 3.7wt% Al2O3, 2.3wt% MgO, and 8wt% ZrO2 as added raw materials. The viscosity of the high-temperature glass melt in this embodiment is 0.744 PaS, the average flexural strength of the six groups of microcrystalline glass samples is 73.49 MPa, and the precipitated main crystalline phases are diopside and Augite.
[0023] Example 5 The difference between this embodiment and Embodiment 1 is that the raw material ratio in this embodiment is: 75wt% high-titanium blast furnace slag high-temperature molten liquid; 5wt% CaO, 12wt% SiO2, 2wt% Al2O3, 2wt% MgO, and 4wt% ZrO2 as added raw materials. The viscosity of the high-temperature glass melt in this embodiment is 0.446 PaS, the average flexural strength of the six groups of microcrystalline glass samples is 108.43 MPa, and the precipitated main crystalline phases are clinopyroxene (Esseneite) and diopside.
[0024] Example 6 The difference between this embodiment and Embodiment 1 is that the raw material ratio in this embodiment is: 65wt% high-titanium blast furnace slag high-temperature molten liquid; 7wt% CaO, 16wt% SiO2, 3wt% Al2O3, 2wt% MgO, and 7wt% ZrO2 as added raw materials. The viscosity of the high-temperature glass melt in this embodiment is 0.634 PaS, the average flexural strength of the six groups of microcrystalline glass samples is 81.21 MPa, and the precipitated main crystalline phases are clinopyroxene (Esseneite) and fassaite-like minerals.
[0025] Example 7 A method for preparing high-titanium blast furnace slag microcrystalline glass includes the following steps: Step 1: Preparation of zirconium oxide-yttrium oxide nucleating agent, specifically including: S11. 10g of zirconium oxide, 0.5g of yttrium oxide and 0.1g of beryllium hydroxide were ball-milled together with high energy and then filtered to obtain a mixture. The high energy ball milling parameters were as follows: yttrium-stabilized zirconium oxide balls were used, the ball-to-material ratio was 10:1, the ball milling medium was liquid nitrogen, and the ball milling was carried out at 600 rpm for 2 hours. S12. Add 10g of the mixture, 1g of polyacrylamide, and 0.5g of sodium bicarbonate to 100g of water. First, heat the mixture at 50℃ for 2 hours, then heat it at 130℃ for 0.5 hours. After cooling, filter and wash to obtain the zirconium oxide-yttrium oxide nucleating agent. S13. Weigh out 1 wt% CaO, 8 wt% SiO2 and 1 wt% zirconium oxide-yttrium oxide nucleating agent as external raw materials. Mix the external raw materials and add them directly to 90 wt% high-titanium blast furnace slag high-temperature molten liquid (1450℃) to obtain high-temperature glass liquid. Step 2: The high-temperature molten glass is rolled into shape using rolling rollers with heat exchange function to obtain the base glass; Step 3: The formed base glass sample is directly subjected to nucleation and crystallization heat treatment using the heat energy exchanged by the calendering roller with heat exchange function to obtain a microcrystalline glass sample. The average flexural strength of the six groups of microcrystalline glass samples is 183.54 MPa, and the main crystalline phase precipitated is monoclinic pyroxene (Esseneite).
[0026] Example 8 A method for preparing high-titanium blast furnace slag microcrystalline glass includes the following steps: Step 1, specifically includes: S11. 10g of zirconium oxide, 0.5g of yttrium oxide and 0.1g of beryllium hydroxide were ball-milled together with high energy and then filtered to obtain a mixture. The high energy ball milling parameters were as follows: yttrium-stabilized zirconium oxide balls were used, the ball-to-material ratio was 10:1, the ball milling medium was liquid nitrogen, and the ball milling was carried out at 600 rpm for 2 hours. S12. Weigh out 1 wt% of CaO, 8 wt% of SiO2 and 1 wt% of zirconium oxide and yttrium oxide after ball milling as external raw materials. Mix the external raw materials and add them directly to 90 wt% of high titanium blast furnace slag high-temperature molten liquid (1450℃) to obtain high-temperature glass liquid. Step 2: The high-temperature molten glass is rolled into shape using rolling rollers with heat exchange function to obtain the base glass; Step 3: The formed base glass sample is directly subjected to nucleation and crystallization heat treatment using the heat energy exchanged by the calendering roller with heat exchange function to obtain a microcrystalline glass sample. The average flexural strength of the six groups of microcrystalline glass samples is 159.54 MPa, and the main crystalline phase precipitated is monoclinic pyroxene (Esseneite).
[0027] Example 9 A method for preparing high-titanium blast furnace slag microcrystalline glass includes the following steps: Step 1: Preparation of zirconium oxide-yttrium oxide nucleating agent, specifically including: S11. Add 10g of zirconium oxide, 1g of polyacrylamide, and 0.5g of sodium bicarbonate to 100g of water, heat at 50℃ for 2h, then heat at 130℃ for 0.5h, cool and filter to obtain modified zirconium oxide nucleating agent. S12. Weigh out 1 wt% CaO, 8 wt% SiO2 and 1 wt% modified zirconium oxide as external raw materials. Mix the external raw materials and add them directly to 90 wt% high-titanium blast furnace slag high-temperature molten liquid (1450℃) to obtain high-temperature glass liquid. Step 2: The high-temperature molten glass is rolled into shape using rolling rollers with heat exchange function to obtain the base glass; Step 3: The formed base glass sample is directly subjected to nucleation and crystallization heat treatment using the heat energy exchanged by the calendering roller with heat exchange function to obtain a microcrystalline glass sample. The average flexural strength of the six groups of microcrystalline glass samples is 167.21 MPa, and the main crystalline phase precipitated is monoclinic pyroxene (Esseneite).
[0028] Example 10 A method for preparing high-titanium blast furnace slag microcrystalline glass includes the following steps: Step 1, specifically includes: S11. 10g of zirconium oxide and 0.1g of beryllium hydroxide were subjected to high-energy ball milling, then filtered and washed to obtain a mixture. The high-energy ball milling parameters were as follows: yttrium-stabilized zirconium oxide balls were used, the ball-to-material ratio was 10:1, the ball milling medium was liquid nitrogen, and the ball milling was carried out at 600 rpm for 2 hours. S12. Weigh out 1 wt% of CaO, 8 wt% of SiO2 and 1 wt% of zirconium oxide and yttrium oxide after ball milling as external raw materials. Mix the external raw materials and add them directly to 90 wt% of high titanium blast furnace slag high-temperature molten liquid (1450℃) to obtain high-temperature glass liquid. Step 2: The high-temperature molten glass is rolled into shape using rolling rollers with heat exchange function to obtain the base glass; Step 3: The formed base glass sample is directly subjected to nucleation and crystallization heat treatment using the heat energy exchanged by the calendering roller with heat exchange function to obtain a microcrystalline glass sample. The average flexural strength of the six groups of microcrystalline glass samples is 144.84 MPa, and the main crystalline phase precipitated is monoclinic pyroxene (Esseneite).
[0029] Comparative Example 1 The difference between this embodiment and Embodiment 1 is that the raw material ratio in this embodiment is as follows: 50wt% high-titanium blast furnace slag high-temperature molten liquid; 7.5wt% CaO, 25.6wt% SiO2, 4.4wt% Al2O3, 6wt% MgO, and 9wt% ZrO2 as added raw materials. The viscosity of the high-temperature glass melt in this embodiment is 0.493 PaS, the average flexural strength of the six groups of microcrystalline glass samples is 60.51 MPa, and the precipitated main crystalline phases are perovskite and a small amount of diopside.
[0030] Comparative Example 2 The difference between this embodiment and Embodiment 1 is that the raw material ratio in this embodiment is: 40wt% high-titanium blast furnace slag high-temperature molten liquid; 11.6wt% CaO, 27.7wt% SiO2, 5.7wt% Al2O3, 4wt% MgO, and 11wt% ZrO2 as added raw materials. The viscosity of the high-temperature glass melt in this embodiment is 0.523 PaS, the average flexural strength of the six groups of microcrystalline glass samples is 35.91 MPa, and the precipitated main crystalline phases are perovskite and a small amount of diopside.
[0031] The microcrystalline glass generated in Examples 1-6 has high flexural strength due to the good composite nucleating agents TiO2 and ZrO2, which effectively promote the crystallization of high-titanium blast furnace slag microcrystalline glass. The microcrystalline glass samples have a high content of diopside or fassaite mineral crystals, which can significantly improve the strength of the microcrystalline glass. Example 7 introduces yttrium oxide as a crystal nucleus and modifies the surface of zirconium oxide and yttrium oxide. Yttrium oxide has good activity and good compatibility with other components. It can also improve the structure of glass crystals, making the bonding between particles tighter and enhancing the strength of the glass. Polyacrylamide modification can enhance the toughness and impact resistance of the glass by adding zirconium oxide and yttrium oxide. The added beryllium hydroxide increases the crystallization rate of the glass-ceramic during the crystallization process. Example 8 only introduces yttrium oxide, which has a limited improvement in impact resistance. The flexural strength of the resulting glass-ceramic is not as good as that of Example 7. Example 9 only modifies with polyacrylamide, and the improvement in the flexural strength of the glass-ceramic is also not as good as that of Example 7. Example 10 only adds beryllium hydroxide, which improves the crystallization rate of the glass-ceramic, but has almost no effect on the flexural strength.
[0032] In Comparative Examples 1 and 2, a larger amount of external raw materials were added, which gradually increased the SiO2 content in the system. As a network formation body, SiO2 also gradually increased the viscosity of the glass melt. In the high-viscosity melt, TiO2 and other nucleating agents are prone to local enrichment, which leads to the formation of a dual structure of "coarse grain region + glass region" in subsequent crystallization. The dispersion of flexural strength is increased, resulting in a decrease in physical properties such as flexural strength.
[0033] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.
Claims
1. A high-titanium blast furnace slag microcrystalline glass, characterized in that, By weight percentage, it includes 60.0-90.0 wt% high-titanium blast furnace slag; The high-titanium blast furnace slag microcrystalline glass contains 10.0-40.0 wt% added raw materials, and its final chemical composition includes: 15-25 wt% CaO, 30-45 wt% SiO2, 10-20 wt% TiO2, 10-20 wt% Al2O3, 1-7 wt% MgO, 1-4 wt% Fe2O3, and 1-10 wt% ZrO2, with the sum of all components being 100 wt%.
2. The high-titanium blast furnace slag microcrystalline glass as described in claim 1, characterized in that, The chemical composition of the high-titanium blast furnace slag includes: 10-30wt% CaO, 10-30wt% SiO2, 10-25wt% TiO2, 10-20wt% Al2O3, 0-15wt% MgO, and 0-5wt% Fe2O3. The added raw materials include 1-8wt% CaO, 8-18wt% SiO2, 0-3.7wt% Al2O3, 0-2.3wt% MgO, and 1-8wt% ZrO.
3. The high-titanium blast furnace slag microcrystalline glass as described in claim 1, characterized in that, TiO2 and ZrO2 serve as nucleating agents for the formation of glass-ceramics.
4. A method for preparing high-titanium blast furnace slag microcrystalline glass as described in claim 1, characterized in that, Includes the following steps: Step 1: Weigh the added raw materials according to the proportion, mix them well, and then add them directly to the high-temperature molten liquid of high-titanium blast furnace slag. Stir evenly to obtain high-temperature glass liquid. Step 2: The high-temperature molten glass is rolled into shape using rolling rollers with heat exchange function to obtain the base glass; Step 3: The formed base glass sample is directly subjected to nucleation and crystallization heat treatment using the heat energy exchanged by the calendering roller with heat exchange function to obtain a microcrystalline glass sample.
5. The method for preparing high-titanium blast furnace slag microcrystalline glass as described in claim 4, characterized in that, In step one, the temperature of the high-titanium blast furnace slag high-temperature molten liquid is 1350~1500℃, and no external heating is required after the addition of external raw materials.
6. The method for preparing high-titanium blast furnace slag microcrystalline glass as described in claim 4, characterized in that, In step two, the high-temperature molten glass passes directly through a rolling mill roller with heat exchange function, without needing to be poured into an external mold for forming.
7. The method for preparing high-titanium blast furnace slag microcrystalline glass as described in claim 4, characterized in that, In step two, the calender roll body with heat exchange function contains a heat exchange medium inside. The heat exchange medium is a fluid or substance that can transfer heat energy during the heat exchange process, including one or more of water, oil, and gallium.
8. The method for preparing high-titanium blast furnace slag microcrystalline glass as described in claim 4, characterized in that, In step one, before adding the external raw material into the high-titanium blast furnace slag high-temperature molten liquid, the zirconium oxide in the external raw material is modified, and the method is as follows: S11. Zirconia, yttrium oxide and beryllium hydroxide are mixed and then subjected to high-energy ball milling, followed by filtration to obtain a mixture; S12. Add the mixture, polyacrylamide, and sodium bicarbonate to water, heat and stir, cool, filter, and wash to obtain zirconium oxide-yttrium oxide nucleating agent.
9. The method for preparing high-titanium blast furnace slag microcrystalline glass as described in claim 8, characterized in that, In S11, the mass ratio of zirconium oxide, yttrium oxide, and beryllium hydroxide is 1:0.05~0.10:0.01~0.
02. The high-energy ball milling parameters are: using yttrium-stabilized zirconium oxide balls, a ball-to-material ratio of 8~10:1, using liquid nitrogen as the ball milling medium, and ball milling at 600~800 rpm for 2~4 hours.
10. The method for preparing high-titanium blast furnace slag microcrystalline glass as described in claim 8, characterized in that, In S12, the mass ratio of the mixture, polyacrylamide, sodium bicarbonate and water is 1:0.1~0.2:0.05~0.10:10~20. When heating, the mixture is first heated at 50~80℃ for 1~2 hours, and then heated at 130~135℃ for 0.5~1 hours.